Characterization of silicon photodiodes for diffuse reflectance signal extraction - Pimenta, Sara (2015)
Early detection of gastrointestinal (GI) can cers is one of most important concerns in medical field. Its detection at the earliest stage is crucial to increase the patient survival chances. Optical signals extraction and analysis, specifically diffuse reflectance and intrinsic fluorescence, may impr ove the ability to detect GI dysplasia, once some morphological and biochemical changes on the tissues (related with early cancer progre ssion) can modify these signals’ shape and intensity. The project under th is paper aims to develop a chip - sized spectros copy microsystem for the early detection of GI cancer. This paper presents the characterization of silicon photodiodes (n+/p - epilayer type) fabricated in a standard 0.7 μm CMOS process, with different dimensions. The main goal is to conclude which photodio de must be fabricated for the microsystem implementation, taking into account its capacity to extract the signals in the relevant spectral band (350 nm – 750 nm), not comprising the microsystem dimensions. With this study , it can be conclude d that the suit able photodiodes for the detection of those spectroscopic signals are the ones with 125 × 125 μm 2 or 100 × 100 μm 2 active area , once their quantum efficiency varies between 20% and 55%, approximately, above 450 nm. In spite of the low photodiod es quantum efficiency (lower than 20%) below 450 nm, the viability of using the 100 × 100 μm 2 photodiode to extract the diffuse reflectance signal, between 350 nm and 750 nm, was proven using a test phantom representative of a GI tissue.